PD-L1 expression in renal cell carcinoma clear cell type is related to unfavorable prognosis. Issue 1 (December 2015) - Leite, Katia; Reis, Sabrina; Junior, José; Zerati, Marcelo; Gomes, Daniel; Camara-Lopes, Luiz; Srougi, Miguel
Abstract Background PD-L1 is a glycoprotein from the family of T-cell co-stimulatory molecules that are constitutively expressed by macrophages. Aberrant expression of PD-L1 is observed in human cancers associated with inhibition of the tumor-directed T-cell immune response. There are few reports in the literature evaluating PD-L1 expression in association to prognosis specifically in renal cell cancer clear cell type (RCC-CC). Methods Immunohistochemistry using a PD-L1 polyclonal antibody was performed on a tissue microarray (TMA) that contained 115 surgical specimens of RCC-CC. Cases were classified based on the absence or presence of staining intensity in the cytoplasm and membranes of the tumor cells. Statistical analysis was used to determine the association of PD-L1 expression with classic prognostic factors and tumor recurrence. Results PD-L1 expression was positive in 56.5 % of tumors. The univariate analysis showed a correlation between PD-L1 expression and nuclear Fuhrman grade (p  = 0.021) and microvascular tumor embolization (p  = 0.039). One hundred and four patients were monitored for a mean time of 115.7 months. Seventeen patients (16.3 %) suffered tumor recurrence. Negative outcomes were associated with higher nuclear grade tumors, PD-L1 expression, and the presence of microvascular invasion. Conclusion Our findings confirm that PD-L1 expression is an important prognostic factor in RCC-CC.